2022
DOI: 10.3390/buildings13010045
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and Hardened Properties of Cementitious Composites Incorporating Firebrick Powder from Construction and Demolition Waste

Abstract: Firebricks are generally used in furnace basins where glass, ceramics, and cement are produced. Firebricks have an important place in construction and demolition waste (CDW). However, there is a limited understanding of the effects on fresh and hardened state properties of cementitious composites. This study investigates the mechanical, physical, and microstructural properties of cementitious composites incorporating firebrick powder (FBP) from CDW. In this regard, the FBP was used at 5, 10, 15, 20, and 25% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These results are similar to Baradaran and Nematzadeh (2017), workability was affected reporting similar significant reductions with slump ranging from 85, 70, 65, 60 and 55 mm as a function of replacing 0, 25, 50, 75 and 100 % refractory material in the concrete mix, respectively. Refractory brick dust is relevant when it is less than that of cement to attribute better workability in concrete (Sevim et al (2023). Consequently, a level of flowability will be achieved by using superplasticizer (Shirani et al, 2021).…”
Section: Slump Testmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to Baradaran and Nematzadeh (2017), workability was affected reporting similar significant reductions with slump ranging from 85, 70, 65, 60 and 55 mm as a function of replacing 0, 25, 50, 75 and 100 % refractory material in the concrete mix, respectively. Refractory brick dust is relevant when it is less than that of cement to attribute better workability in concrete (Sevim et al (2023). Consequently, a level of flowability will be achieved by using superplasticizer (Shirani et al, 2021).…”
Section: Slump Testmentioning
confidence: 99%
“…According to studies by Baradaran and Nematzadeh (2017), it was concluded that workability is affected with doses of 25, 50, 75 and 100 % of refractory material, with slump ranging from 70 mm to 55 mm. On the other hand, the specific surface area of materials such as refractory brick powder is relevant when it is lower than that of cement to attribute a better workability in concrete as expressed by Sevim et al (2023). Consequently, a level of flowability is achieved using superplasticizer (Shirani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts have concentrated on diminishing the environmental footprint of OPC by incorporating supplementary cementitious materials (SCMs) like fly ash (FA) and blast furnace slag (BFS). These materials have gained widespread adoption as partial substitutes for OPC, as demonstrated in various studies [9][10][11][12][13][14][15][16][17]. Furthermore, extensive research has been conducted on the utilization of BFS and FA as exclusive or combined constituents in alkali-activated concrete formulations, reporting interesting findings documented in the literature [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 98%
“…Table 1 provides a glimpse of previously proposed concrete strength prediction models utilizing UPV. These models can be broadly categorized into ‘early age’, ‘middle age’, and ‘high temperature’ [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Studies for predicting concrete strength using UPV, which were previously performed, can be divided into three main purposes.…”
Section: Introductionmentioning
confidence: 99%